Edukasi Teknologi Pirolisis untuk Pengolahan Sampah di Kawasan Wisata Hutan Bambu Bekasi - Hanaseta, Evelyne; Maharani, Maya D. D.; Handayani, Lidia; Ariwibowo, Felisha Belva Putri (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Waste management is an environmental issue that is very close to the community, but the problem of waste in tourism areas needs to be carried out more independently. Garbage at tourist attractions consists of packaging and food waste. Plastic packaging is often found in food and drinks, which makes it difficult for nature to break down. The pyrolysis method introduced to the management of the bamboo forest tourist area in Bekasi City can be used to process plastic waste so that plastic waste can be reduced and the amount of plastic waste in the landfill can also be reduced. Pyrolysis education can be an option for onsite waste processing, with the result being oil similar to kerosene.